KAJIAN PENGARUH PERBANDINGAN CAMPURAN SEMEN DAN PASIR SEBAGAI FILTER MORTAR TERHADAP POROSITAS DAN PERMEABILITAS - , SETYO ARI NUGRAHA, Prof. Dr. Ir. Fatchan Nurochmad, M.Agr ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Filtration is a separation process of solid material from fluid (liquid or gas) that carried them by using a porous medium. Filtration is used to remove as much as possible of suspended fine solids and koloid. The mortar filter is a filtration medium made of mixed fine aggregate, cement, water in certain ratio. The mortar filter is a latest inovation in water filtration field. The ability of the mortar filter to remove suspended fine solids and koloid greatly influenced by the porosity and permeability. The final project research discuss porosity and permeability of the mortar filter with their relation. Porosity study was conducted to identify the volume of pores between material within the mortar filter, while the permeability investigation was conducted to provided an overview of the ability of the filter media to deliver water. Porosity and permeability research of the mortar filter was conducted using cement and sand ratio of 1:4, 1:6, 1:8, 1:10 and 1:12. Sand composition on a certain ratio consist of 20 % of sand retained sieves by 0,425 mm, 0,6 mm, 0,85 mm, 1,0 mm and 1,4 mm. The porosity study was conducted by measuring water weight before the mortar filter soaked, and the water weight after one hour the mortar filter soaked. The permeability study was done by retrieving water volume that came out from mortar filter in certain time interval, and record the energy height on the manometer. The permeability research was done with different pressure height between reservoir's tub water surface and the water surface of the outlet faucet of that is 25 cm, 50 cm, 75 cm, 100 cm, 125 cm, 150 cm and 175 cm. Results obtained from the porosity test show that cement sand ratio of 1:10 has the highest porosity with value 20,73 %, followed by 1:12 with value 20,19 %, 1:8 with value 18,74 %, 1:6 with value 16,91 % and 1:4 with value 11,78 %. This suggests that the higher the ratio of cement and sand on the mortar filter, then the higher the porosity values. However, this does not happen in the 1:12 ratio because maximum porosity in the mortar filter occurred at 1:10 ratio. Results obtained from the permeability test show that cement sand ratio of 1:10 has the highest permeability followed by 1:8, 1:12, 1:6 and 1:4. This suggests that the higher the ratio of cement and sand on the mortar filter, then the higher the permeability values. However, this does not happen in the 1:12 ratio due to changes in pore distribution at the time assembly of the mortar filter into the main filter. In addition, the relations between permeability and difference of pressure height is the higher pressure difference between water surface of the reservoir's tub and the outlet faucet, then the smaller the permeability value of the mortar filter. The relations between porosity and permeability can be concluded that the higher the porosity value of the mortar filter, the higher the permeability value. However, this does not occur in cement and sand ratio 1:12.